2020
DOI: 10.1007/s10701-020-00341-9
|View full text |Cite
|
Sign up to set email alerts
|

SICs: Some Explanations

Abstract: The problem of constructing maximal equiangular tight frames or SICs was raised by Zauner in 1998. Four years ago it was realized that the problem is closely connected to a major open problem in number theory. We discuss why such a connection was perhaps to be expected, and give a simplified sketch of some developments that have taken place in the past 4 years. The aim, so far unfulfilled, is to prove existence of SICs in an infinite sequence of dimensions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…5 we conclude that Tr(π 0 ⊗ ρ ′ 0 + π ′ 0 ⊗ ρ 0 ) = 0 and for any a = (0, 0):Tr (π 0 ⊗ ρ ′ 0 + π ′ 0 ⊗ ρ 0 )W † a ⊗ W a = 1. (4.11)But if a 1 = 0 and a 2 = 0 then for a = (a 1 , a 2 ) we have Tr(π 0 W a ) = 0|W a |0 = 0 and Tr(ρ0 W a ) = 0|F † W a F |0 = 0|W (a 2 ,−a 1 ) |0 = 0, hence Tr (π 0 ⊗ ρ ′ 0 + π ′ 0 ⊗ ρ 0 )W † a ⊗ W a = 0a contradiction.You may ask what WH covariant solutions at 0 evade this proof.…”
mentioning
confidence: 74%
“…5 we conclude that Tr(π 0 ⊗ ρ ′ 0 + π ′ 0 ⊗ ρ 0 ) = 0 and for any a = (0, 0):Tr (π 0 ⊗ ρ ′ 0 + π ′ 0 ⊗ ρ 0 )W † a ⊗ W a = 1. (4.11)But if a 1 = 0 and a 2 = 0 then for a = (a 1 , a 2 ) we have Tr(π 0 W a ) = 0|W a |0 = 0 and Tr(ρ0 W a ) = 0|F † W a F |0 = 0|W (a 2 ,−a 1 ) |0 = 0, hence Tr (π 0 ⊗ ρ ′ 0 + π ′ 0 ⊗ ρ 0 )W † a ⊗ W a = 0a contradiction.You may ask what WH covariant solutions at 0 evade this proof.…”
mentioning
confidence: 74%
“…⊗ 1 d we obtain a set of (d − 2) 2 equiangular tight frames, all of them spanning some d(d − 1)/2 dimensional subspace. We can regard the resulting set of subspaces as so many points in a Grassmannian, and then it can be shown that these points are equidistant with respect to the natural metric on the Grassmannian [23].…”
Section: Aligned Sics and Proto-sicsmentioning
confidence: 99%
“…This scheme, often called SIC in the literature, is proven to be optimal for quantum state tomography [8]. Such a particular generalized measurements known for a fast-growing number of dimensions [13,14,15,16,17], but its existence for an arbitrary N has not yet been established [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Zauner conjectured [24,25] that such ensembles exist for any N . Analytic constructions are known [17,14] for all dimensions N ≤ 53, while numerical solutions were obtained [13,18,26] for dimensions N ≤ 193, with some additional solutions known for certain dimensions [15,16,19] up to N = 2208.…”
Section: Introductionmentioning
confidence: 99%